(untitled) (Palimpsesto, 2017)
This article examines the instrumental operating of the administration of justice in the XVII-XVIII Chile, highlighting the Chamber Fines’ management. Three aspects, important to the history of justice, can be outlined: the debts, originating from the administration the Chamber Fines and their collection, set the articulation between justice and good government; writs delivered within the proceedings shed light on various agents and the way they become creditors of the Chamber Fines; records of the fines, and the prosecution for their collection, give rise to negociations between creditors. This allows to put a question to the social economy of justice, and the ways we intend to understand the administration of justice in Hispanic America.